Atmospheric Reaction Chemistry - Akimoto, Hajime (Springer Atmospheric Sciences,, 2016)
This book is aimed at graduate students and research scientists interested in gaining a deeper understanding of atmospheric chemistry, fundamental photochemistry, and gas phase and heterogeneous reaction kinetics. It also provides all necessary spectroscopic and kinetic data, which should be useful as reference sources for research scientists in atmospheric chemistry. As an application of reaction chemistry, it provides chapters on tropospheric and stratospheric reaction chemistry, covering tropospheric ozone and photochemical oxidant formation, stratospheric ozone depletion and sulfur chemistry related to acid deposition and the stratospheric aerosol layer. This book is intended not only for students of chemistry but also particularly for non-chemistry students who are studying meteorology, radiation physics, engineering, and ecology/biology and who wish to find a useful source on reaction chemistry.